المؤثرون الاجتماعيون ودورهم في تعزيز العمل التطوعي - ملك جريدان; إكرام فواري; د/علي ساحي (جامعة عمار ثليجي الاغواط, 2023)
 ملخص الدراسة: تهدف هذه الدراسة للتعرف على دور المؤثرون الاجتماعيون المستخدمين للانستغرام في تعزيز العمل الجمعوي لدى طلبة جامعة عمار ثليجي بالأغواط، والكشف عن الأسلوب الذي يستخدمه المؤثرون على الطلبة بهدف تعزيز العمل الجمعوي، ومعرفة الأعمال التطوعية التي يحث عليها المؤثرون الاجتماعيون عبر الانستغرام. والتعرف على مدى تفاعل طلبة جامعة عمار ثليجي بالأغواط مع الأعمال التطوعية للمؤثرون الاجتماعيون. وكانت إشكالية دراستنا تتمحور حول: ما هو دور المؤثرون الاجتماعيون المستخدمين للانستغرام في تعزيز العمل الجمعوي لدى طلبة جامعة عمار ثليجي بالأغواط؟ وكان المنهج المناسب لهذه الدراسة هو: المنهج الوصفي، ويتمثل مجتمع دراستنا في طلبة جامعة عمار ثليجي بالأغواط. حيث اعتمدنا على العينة القصدية وقصدنا 150 مفردة من الجامعة. وتمكنا من الوصول لهم عبر استمارة الاستبيان الإلكتروني، كانت مدة الدراسة ما بين شهري نوفمبر 2022 وماي2023. توصلت الدراسة للعديد من النتائج أهمها: يتصفح أفراد العينة عبر الانستغرام المضامين الاجتماعية والثقافية، المحتوى الذي يزيد من اهتمامات أفراد العينة هو محتوى اجتماعي (تطوعي) بالدرجة الأولى، ومحتوى تسويقي بالدرجة الثانية، أفراد العينة يرون أن المؤثرون الذين يتابعونهم يحثون على العمل التطوعي. الأسلوب الذي يستخدمه المؤثرون على الطلبة بهدف تعزيز العمل الجمعوي هو أسلوب عقلي. الكلمات المفتاحية: المؤثرون الاجتماعيون – الانستغرام – العمل التطوعي.  Summary of the study: This study aims to identify the role of social influencers who use Instagram in promoting collective work among students of Ammar Thaliji University in Laghouat, and to reveal the method used by influencers on students in order to enhance collective work, and to know the voluntary actions that social influencers urge through Instagram. And to know the extent of the interaction of the students of Ammar Thaliji University in Laghouat with the voluntary work of social influencers. The problem of our study revolved around: What is the role of social influencers who use Instagram in promoting collective work among students of Ammar Thaliji University in Laghouat? The appropriate approach for this study was: the descriptive approach, and the population of our study is the students of Ammar Thaliji University in Laghouat. Where we relied on the intentional sample and intended 150 items from the university. We were able to reach them through the electronic questionnaire. The study period was between November 2022 and May 2023. The study reached many results, the most important of which are: the respondents browse social and cultural contents through Instagram, the content that increases the interests of the respondents is social (voluntary) content in the first place, and marketing content in the second degree, the respondents see that the influencers who follow them urge volunteer work. The method used by those influencing students to promote collective action is a mental method. Keywords: social influencers - Instagram - volunteer work
دراسة ميدانية على عينة من مستخدمي الانستغرام طلبة جامعة عمار ثليجي بالأغواط